Clinical outcome in lung cancer with a second malignancy: The time sequence matters. Issue 43 (October 2016) - Lu, Ming-Shian; Chen, Miao-Fen; Huang, Yao-Kuang; Liu, Hui-Ping; Tsai, Ying-Huang
Abstract : Abstract: The aim of the study was to determine the clinical outcome of lung cancer patients with a secondary malignancy according to the time sequence between the lung cancer and the secondary malignancy. Retrospective review of all lung cancer patients with any secondary cancer treated from June 2004 to July 2012. The survival of patients with a secondary malignancy was compared to those patients without a secondary malignancy. According to the time sequence between the lung cancer and the secondary malignancy, patients were divided into 4 groups. Group I: lung cancer without any other malignancy, Group II: lung cancer with a secondary malignancy at follow-up, Group III: lung cancer with a pre-existing malignancy, Group IV: synchronous malignancies (diagnosis interval between lung cancer and a secondary malignancy of less than 3 months). Patients with any secondary cancer in their history or at follow up included 157 patients (9.5%). Collectively; the median survival was significantly better for patients with a secondary malignancy, 19.09 months, compared to those without a secondary malignancy, 9.53 months, P  < 0.001, HR 0.66 (95% CI 0.55 – 0.79). However, the survival differed significantly according to the time sequence between the lung cancer and the secondary malignancy. The median survival was 47.9 months for group II patients, 12.19 months for group III, 17.51 months for group IV, and 9.53 months for group I; P = 0.001. In Cox proportional hazard analysis, the risk of dying decreased by 68% in group II patients compared to group I patients, HR 0.32 (95% CI 0.21–0.5), P  < 0.001. Although the risk of dying for group III and IV decreased by 19% and 16% respectively compared to group I patients, it did not reach statistical significance. Nowadays, secondary malignancy in lung cancer patients is a frequent finding. Better survival was observed for patient with secondary malignancy following lung cancer.